Ports and fortifications in the Muslim World : coastal military architecture from the Arab Conquest to the Ottoman Period - Pradines, Stéphane, (Fouilles de l'Institut français d'archéologie orientale du Caire ;, 2020)
Harbors; Islamic Empire; history, Military.